One-Year Clinical Outcome in Middle Eastern Patients with Atrial Fibrillation: The Jordan Atrial Fibrillation (JoFib) Study - Ayman Hammoudeh; Yousef Khader; Ramzi Tabbalat; Yahya Badaineh; Nazih Kadri; Haneen Shawer; Eyas Al-Mousa; Rasheed Ibdah; Batool A. Shawer; Imad A. Alhaddad (International Journal of Vascular Medicine)
Background. Prevention of stroke and systemic embolism (SE) prevention in patients with atrial fibrillation (AF) has radically changed in recent years. Data on contemporary utilization of oral anticoagulants (OACs) and cardiovascular outcome in Middle Eastern patients with AF are needed. Methods. The Jordan atrial fibrillation (JoFib) study enrolled consecutive patients with AF in Jordan from May 2019 through October 2020 and were followed up for one year after enrollment. Results. Overall, 2020 patients were enrolled. The mean age was 67.9+13.0 years. Nonvalvular (NVAF) was diagnosed in 1849 (91.5%) patients. OACs were used in 85.7% of high-risk patients with NVAF (CHA2DS2-VASc score>3 in women, and>2 in men), including direct OACs (DOACs) in 64.1% and vitamin K antagonists (VKA) in 35.9%. Adherence rate to the use of the same OAC agent was 90.6% of patients. One-year cardiovascular (CV) mortality was 7.8%, stroke/SE was 4.5%, and major bleeding events were 2.6%. Independent predictors for all-cause mortality in patients with NVAF were age>75 years, heart failure, major bleeding event, type 2 diabetes mellitus, study enrollment as an in-patient, and coronary heart disease. The use of OACs was associated with lower all-cause mortality. The strongest independent predictors for stroke/SE were high-risk CHA2DS2-VASc score and prior history of stroke. Conclusions. This study of Middle Eastern AF patients has reported high adherence to OACs. The use of OACs was associated with a lower risk for all-cause mortality. One-year rates of stroke and major bleeding events were comparable to those reported from other regions in the world.